Frequency and causes of mortality in patients with stroke referred to Zahedan city hospital in 2016 - Khosravi, Alireza; Amirifard, Hamed; Karami, Fatemeh (International Journal of Research in Medical Sciences, 2018)
Background: Stroke is the fifth common cause of mortality worldwide. This study was conducted with the aim of Evaluation of mortality rate and its causes in patients with stroke referred to Zahedan city hospital. Methods: This was a cross-sectional study that conducted on 320 patients with stroke. Data collected by a checklist and then analyzed by statistical methods in SPSS.19. Results: Of all patients, 59.7% were male and 40.3% were female. The mean age of patients was 63.18±13.85 years. 76% of the strokes were ischemic and 24% were hemorrhagic. The mortality rate in this study was 16.3% which was not correlated with age, gender and type of stroke. The most common cause of mortality was pneumonia aspiration with 36.5 % and then sepsis with 32.7%. Conclusions: In overall, this study showed that mortality rate was 16.3 % and the most common cause of mortality was pneumonia aspiration and sepsis.